Gender and language in the labour market - Mikić, Jasna (Teorija in praksa, 2021)
The present article explores the use of grammatical forms in job advertisements published over the past 60 years (1958, 1978, 1998 and 2018). A historical examination of the use of gender forms in employment is based on analysis of job advertisements published in the Slovenian language, and the particular socio-economic context. The results show that the frequency of use of the masculine, feminine and neutral forms has not drastically altered over the decades. In general, feminine and neutral forms were used less frequently, and the masculine grammatical form consistently dominates. In 2018, the latter was seemingly neutralised by adding the abbreviation M/F.
Keywords: Advertising; Gender studies; Grammar; Labor market; moška slovnična oblika; Oglaševanje; Slovenian language; Slovenščina; Slovnica; Študije spolov; Trg dela; zaposlitveni oglasi